Komunikasi Pengambilan Keputusan Selama Pernikahan Pada Laki-Laki yang Menikah di Usia Anak Karena Hamil di Luar Nikah - Nurul Syifa, Salsa; Ratri Rahmiaji, Lintang; Hasfi, Nurul (Interaksi Online, 2024)
The high rate of child marriage in Indonesia, largely driven by out-of-wedlock pregnancies, has presented a series of complex challenges for the men involved. These individuals face significant emotional, social, and economic pressures, including demands to drop out of school and the risk of experiencing depression and loneliness. Additionally, child marriages are often prone to divorce and domestic violence (DV), primarily due to the lack of emotional maturity and poor communication between partners. This study aims to explore the narrative of decision-making during marriage among men who married at a young age due to out-of-wedlock pregnancies. Through in-depth interviews with three informants who experienced child marriage, this research examines how communication influences the decision to marry at a young age, as well as the decisions made throughout the marriage. The study employs Labov's narrative analysis method to delve into and understand this process. The results of this study show that decision-making among men who marry at a young age involves a series of stages, whether in facing premarital pregnancy, economic crises, family planning, or decisions regarding domestic violence (DV) and divorce. Initially, they experience confusion and uncertainty, but with pressure from family and financial situations, they take steps to adapt to their new responsibilities. Decisions to marry and face economic challenges are made through cooperation and open communication with their partners. In terms of family planning, wives tend to take a more dominant role, while husbands support them through full trust. Furthermore, the rejection of DV and divorce reflects an awareness that conflicts can be resolved through patience and thoughtful discussion, indicating a commitment to the continuity of marriage.